Intelligent excitation adaptability for full-spectrum real-time vibration isolation - Shuai Chen; Yilong Wang; Qianjing Wu; Hesheng Han; Dengqing Cao; Biao Wang (Communications Engineering)
Abstract Vibration isolation systems frequently face challenges in varying environments due to their inherent resonance effects and responsive delays. Here, we report an intelligent excitation-adaptative vibration isolation (IEA-VI) architecture that mimics the biological adaptive mechanism of human muscle, enabling real-time stiffness adjustment to mitigate variable environmental impacts through sensing, processing, and controlling modules. The IEA-VI system operates in high-static-low-dynamic-stiffness and high-dynamic-stiffness modes, capable of intelligent on-demand mode switching. We develop a real-time frequency perception algorithm to quickly perceive excitation frequencies, enabling the system to perform rapid mode-switching and thus achieve real-time full-spectrum vibration control. We design and fabricate a proof-of-concept IEA-VI system and theoretically and experimentally demonstrate that the system’s frequency perception is approximately 10 times faster than that achieved with the commonly used Fast Fourier Transform at low frequencies. Meanwhile, the system effectively mitigates resonance and delivers high-performance vibration isolation through intelligent real-time mode switching.